Life of an expat - Jaroslav, Najman (Machart, 2023)
This book describes - in English the author's emigration from Czechoslovakia triggered by a historical event in August 1968. All events in this book are based on recollection of the author's memories and historical photos from his archives. Only a minor part of the events was collected from friends and colleagues. There might be some discrepancies regarding the exact locations and dates. The book reflects his personal opinions and feelings, and it does open broad his private life. The book represents a complete emigration circle. It starts in Czechoslovakia in 1968 and ends after the author returns to the Czech Republic and regains his citizenship at the end of 2000.
Keywords: Memoáry, osobnosti a osudy